Climbing Together: Relational Morality and Meaningful Action in Intercultural Community Engagement - Taft, Anna (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
Scholars and commentators have noted the frequent inefficacy of "development," and criticized the power relations it entrenches. Aware of these problems, some North Americans choose to disengage from transnational work. But the reality is that we cannot avoid participating in global networks that affect people in many countries, and there are vast inequalities in access to resources that need to be addressed. Through philosophical insights, narrative accounts, and testimony from community members, we can discover a path between development and disengagement, through which relational morality and meaningful action can enrich intercultural collaboration and yield many fruits.